Structure and Properties of Ti–O–N Coatings Produced by Reactive Magnetron Sputtering; Russian Physics Journal; Vol. 56, iss. 10 - Konishchev M. E. Maksim Evgenievich; Kuzmin O. S. Oleg Stanislavovich; Pustovalova A. A. Alla Aleksandrovna; Морозова Н. С. Наталья Сергеевна; Evdokimov K. E. Kirill Evgenievich; Surmenev R. A. Roman Anatolievich; Pichugin V. F. Vladimir Fyodorovich; Epple M. K. Mattias Kristian (2014, 2014)
Title screen